PEMETAAN EFEK SPASIAL KEMISKINAN SELURUH KABUPATEN DI INDONESIA - Hasibuan, Sarah; Hasibuan, Mutia Harum (REKSABUMI, 2022)
Poverty is one of the obstacles to the difficulty of the country development. Poverty causes adecrease of human resources quality, inability to access education, health, good nutrition whichresults in productivity degradation. The purpose of this study are to analyze the pattern of spatialpoverty all regencies in Indonesia using the Moran’s Index and looks at the local spatial distributionof poverty using the Local Indicator of Spatial Autocorrelation (LISA) approach. This study uses thedata period in 2019. The results of this study show that pockets of poverty in Indonesia are mostlylocated in the provinces of Papua, West Papua and East Nusa Tenggara. The regencies with thelowest poverty are found in the regencies of Bali and South Kalimantan Provinces. Moran's Testshowed a positive autocorrelation of 0.474259 which indicates a general spatial autocorrelationacross all regency in Indonesia with a clusted pattern. The LISA test showed poverty level of thepopulation was clustered into four groups, namely: 50 regencies that were in the high povertyregencies surrounded by high poverty (high-high), 69 regencies in low poverty criteria surroundedby low poverty regencies (low-low), 12 regencies in the low poverty, surrounded by high poverty(low-high) and 5 high poverty regencies surrounded by low poverty (high-low). Thus, this studyproves that poverty reduction must be based on the uniqueness and characteristics of each region.